Foreign policies of the major powers : politics and diplomacy since world warII / edited by Pauline Eadis and Lloyd Pettifer - White, Chris (ed.) (New Delhi, 2013)
This is a comprehensive collection of materials related to the foreign policies of great powers since the end of World War II. The editors have rendered scholars a great service by means of the acuity of their choice of materials and the accessibility to them which these volumes now accord.$1 (BStephen Chan, Professor of International Relations, School of Oriental and African Studies An understanding of foreign policy is of importance not only to professionals and scholars in international relations but also to the many international and multinational corporations with business interests in different parts of the world. Those who need to gain a rapid yet authoritative understanding of the foreign policies of the major powers should find this set to be of use. The four volumes - covering the USA, the Soviet Union and present-day Russia, China and Japan and the European Union - form a timely comprehensive and up-to-date account of the major debates and developments of the world$1 (Bs major powers.s
volume 4 : Europe
Keywords: Foreign policy-United States